Enhance critical thinking in physical education among Malaysian university students - Abdullah, Borhannudin; Badiei, Mina; Sulaiman, Tajularipin; Baki, Roselan (Scientific & Academic Publishing, 2014)
The paper gives information of the importance of Critical Thinking (CT) and its role in physical education. Furthermore, it is going to review the dispositions of critical thinking and explores the answer to two questions: How can critical thinking relate to the area of physical education and sport? How can be CT used in fields of sports or within the physical education lesson? According to the experimental survey, the findings indicated that the level of CT dispositions was moderate for all subscales. The result also shows the highest correlation between harmonious passion and critical thinking disposition (r = .240, p< 0.01) as well as there is a low correlation between passion criteria with open-mindedness and systematicity (r = .157, p< .05). Therefore, the students need more critical thinking activities to enhance their ability and skill and if sstudents show a strong passion toward an action which they like most, they will perform better in physical activities.